Pengaruh Pola Asuh Demokrasi dan Kecerdasan Emosi Terhadap Pertimbangan Moral Siswa - Jontrianto, Jontrianto; Menanti, Asih; Lubis, M Rajab (Universitas Persatuan Guru 1945 NTT, 2019)
This study aims to (1) determine the effect of democracy parenting style and emotional intelligence with moral judgment (2) to determine the effect of democracy parenting style with moral judgment (3) to determine the effect of emotional intelligence with moral judgment. The population of this study are students of class XI SMAN 12 Medan amounted to 344 students. The study sample consisted of 105 students who were selected using the proportionate stratified random sampling technique. Collected using the moral judgment scale used are defining issues test (DIT), a scale of democracy parenting style, and emotional intelligence scale. Data were analyzed using regression analysis techniques. The results show (1) there is no effect of democracy parenting style on students' moral judgment, which is indicated by the coefficients rx1y = 0.448 and p > 0.05 ; (2) there is no effect of emotional intelligence on students' moral judgment, which is indicated by the coefficients rx1y = 0.161 and p > 0.05 ; (3) there is no effect of democracy parenting style and emotional intelligence with students' moral judgment, which is indicated by the coefficients F = 1.243 and R = 0.154 while RÂ² = 0.024 with p > 0.05. The percentage of contributions given by democracy parenting style and emotional intelligence towards moral judgment is 24 %. The remaining 76 % is influenced by other variables not examined in this study.